Hubungan Disfungsional Family dan Triangular of Love pada Remaja yang Sedang Menjalin Hubungan Romantis - Sudrajat, Zahra Kayla; Sahrani, Riana (Lembaga Yasin AlSys, 2025)
Adolescence is a developmental phase characterized by identity formation, emotion regulation, and increasingly complex interpersonal relationships, in which family experiences play a crucial role in shaping the dynamics of romantic relationships, including how adolescents develop intimacy, passion, and commitment as described in Sternberg’s Triangular Theory of Love. Although dysfunctional families are known to disrupt emotional development and relationship quality, studies that specifically examine how such conditions affect the components of love in adolescents remain limited. This study aims to determine the relationship between family dysfunction and the Triangular Theory of Love among adolescents who are currently in romantic relationships. A quantitative method with purposive sampling was employed, involving 280 adolescents aged 17–24 years who met the research criteria. Data were collected through an online questionnaire using the Family Assessment Device (FAD) to measure the level of family dysfunction and Sternberg’s Triangular Love Scale (STLS) to measure intimacy, passion, and commitment, and were then analyzed through validity and reliability testing, assumption testing, and Pearson correlation analysis. The results show that most respondents fall into the low family dysfunction category and report generally high love quality, particularly in the dimensions of intimacy and commitment. Correlation analysis reveals a significant negative relationship between family dysfunction and love quality (r = –0.199; p < 0.001), indicating that the higher the level of family dysfunction, the lower the quality of intimacy, passion, and commitment in adolescents’ romantic relationships. These findings underscore the importance of functional family conditions in fostering healthy romantic relationship quality among adolescents and provide an empirical basis for the development of family-based interventions and adolescent mentoring programs in educational and psychosocial service contexts.